Association of Methylenetetrahydrofolate Reductase Gene rs1801133 Polymorphism and Controlling Nutritional Status (CONUT) Score with Colorectal Cancer Susceptibility - Zhang Z; Wu Z; Zeng Y; Li Y; Feng Y; Gao Z; Chen Y (International Journal of General Medicine)
Zhuoxin Zhang,1 Zuguang Wu,1 Yuwen Zeng,1 Yunlin Li,1 Yingchuan Feng,1 Zhen Gao,1 Yijin Chen2 1Department of Gastrointestinal Surgery, Meizhou People’s Hospital, Meizhou, People’s Republic of China; 2Department of Gastroenterology, Meizhou People’s Hospital, Meizhou, People’s Republic of ChinaCorrespondence: Yijin Chen, Department of Gastroenterology, Meizhou People’s Hospital, Meizhou, People’s Republic of China, Email yijinchenmz@163.comBackground: Susceptibility to some cancers is linked to methylenetetrahydrofolate reductase (MTHFR) polymorphisms and the Controlling Nutritional Status (CONUT) score in some populations. However, their relationship with susceptibility to colorectal cancer (CRC) susceptibility in the Hakka Chinese population remains unclear.Methods: In total, 620 CRC patients and 734 controls were enrolled. MTHFR rs1801133 was genotyped, medical records (age, sex, smoking history, alcohol consumption, hypertension, diabetes mellitus, and family history of cancer, and blood cell parameters) were collected, and the relationship between this information and CRC susceptibility was analyzed.Results: There were significant differences in the distribution of CONUT classification (p= 0.002), and proportions of history of smoking (p